Enhancement of broadband ultraviolet visible photodetection by boron nitride nanoparticles in bulk graphene oxide layer - Ahmad, Harith; Thandavan, Tamil Many K. (Elsevier, 2018)
A proposed boron nitride/graphene oxide (BN/GO) composite photodetector (PD) was prepared using a drop cast method for photodetection in the ultraviolet (UV) and visible light ranges. Morphology of the GO, distribution of BN nanoparticles and composition of B, N, C and O elements were confirmed by field emission scanning electron microscope (FESEM) analysis and energy dispersive x-ray (EDX) spectroscopy results. Raman scattering indicates high frequency intrinsic E2g vibrations at 1349 cm−1 and low intense peaks at 803 cm−1 from hexagonal BN (h-BN) structures in the bulk GO layer, while an overlap in the D and G bands at 1349 and 1581 cm−1 respectively indicates the presence of the GO layer. Excellent photoconduction of 380 and 405 nm UV sources and a 650 nm red laser source showed that the measured photocurrent is dependent on power regardless of the signal wavelength. Variations in sensitivity allow the device to be operated at selected direct current (DC) bias voltages, while high frequency modulation at 1000 Hz showed a profound rise and fall time about 13.6 and 245.6 μs respectively. Characteristics as self-powered PD was observed, has an enhancement about 3450% at its zero bias voltage.